Effect of egg yolk freezing on properties of mayonnaise. (May 2016) - Huang, Liyan; Wang, Tong; Han, Zhaopeng; Meng, Yanli; Lu, Xiaoming
Abstract: We hypothesized that the properties of mayonnaise will be affected by egg yolk with different freezing storage time. In this work, liquid yolk was stored at temperature of −18 °C for 0, 30, 60, 90, 120 days. The properties of mayonnaise prepared with frozen yolks were characterized. Mayonnaise heat stability, color and rheological characteristics were evaluated. The microstructure, and sensory properties of the mayonnaise were also examined. The secondary structure of proteins of the yolk stored for different time was characterized using circular dichroism spectra (CD). Compared with mayonnaise prepared with fresh yolk, mayonnaise made with frozen yolk had increased values of hardness. Color determination showed that the lightness of the mayonnaise increased, but redness/yellowness decreased. The rheological measurements indicated that flow behaviors of all samples could be modeled by the Herschel–Bulkley law model. Microscopic observation showed the size of oil droplet in mayonnaise became bigger at 30 d freezing (M3). The secondary structure evaluation of frozen yolk showed that after 60 days freezing storage, the yolk protein became markedly more hydrophobic. Furthermore, sensory evaluation showed that mayonnaise made with frozen yolk was more acceptable than that made with fresh yolk. Graphical abstract: SEM micrographs of mayonnaise products. Magnification is 5000×. Highlights: We examine the properties of mayonnaise prepared with yolks frozen different days. Different stages of changes in physiochemical properties during frozen storage. Yolk freezing decreased heat stability of mayonnaise. Gelation transition temperature of all samples decreased because of yolk freezing. M6 and/or Y6 show singular property.